Musculoskeletal Interventions / Techniques for Therapeutic Exercise: Third Edition - Hoogenboom Barbara J; Prentice William E; Voight Michael L (Mcgraw Hill Education, 2014)
This book is a comprehensive guide to the system considerations, design, implementation, and progression of rehabilitation programs for musculoskeletal injuries and dysfunction. Preface, Acknowledgements, Foundations of the Rehabilitation Process, Introduction to Therapeutic Interventions: The Guide to Physical Therapist Practice and Clinical Reasoning and an Algorithmic-Approach to Intervention, Understanding and Managing the Healing Process Through Rehabilitation, Neuromuscular Scan Examination, Impairments Caused by Pain, Impaired Posture and Function, Treating Physiologic Impairments During Rehabilitation, Impaired Muscle Performance: Regaining Muscular Strength and Endurance and Power, Impaired Endurance: Maintaining Aerobic Capacity and Endurance, Impaired Mobility: Restoring Range of Motion and Improving Flexibility, Impaired Neuromuscular Control: Reactive Neuromuscular Training, The Tools of Rehabilitation, Plyometric Exercise in Rehabilitation, Open - Versus Closed Kinetic Chain Exercise in Rehabilitation, Proprioceptive Neuromuscular Facilitation Techniques in Rehabilitation, Joint Mobilization and Traction Techniques in Rehabilitation, Regaining Postural Stability and Balance, Establishing Core Stability in Rehabilitation, Aquatic Therapy in Rehabilitation, Functional Movement Assessment, Functional Exercise Progression and Functional Testing in Rehabilitation, Functional Training and Advanced Rehabilitation, Intervention Strategies for Specific Injuries, Rehabilitation of Shoulder Injuries, Rehabilitation of the Elbow, Rehabilitation of Wrist and Hand and Digits, Rehabilitation of the Groin and Hip and Thigh, Rehabilitation of the Ankle and Foot, Cervical and Thoracic Spine, Rehabilitation of Injuries to the Lumbar and Sacral Spine, Special Consideration for Specific Patient Populations, Rehabilitation Considerations for the Older Adult, Considerations for the Pediatric Patient, Considerations for the Physically Active Female, Index.